Recent Patents on Wall Climbing Robot with Negative Pressure Adsorption - Tang, Dedong (Recent Patents on Engineering, 2019)
Background: The wall climbing robot is an automatic mechanical device capable of being adsorbed on the wall surface and carrying out various predetermined work. Compared with human labor, the wall climbing robot has the advantages of high efficiency, low cost and stable operation quality. It can replace human beings to accomplish various dangerous work, reduce the risk and labor intensity of high-altitude operation, and greatly promote the improvement of productivity. At present, wall climbing robot has been widely used in the construction industry, fire control, nuclear industry, petrochemical industry and manufacturing industry. Objective: I will review related patents of wall climbing robot with negative pressure adsorption and illustrate their structure and working principle. The results of the analysis can provide some meaningful reference for the optimal design of this kind of robot. Methods: Based on the comparative analysis for the latest patents related to wall climbing robot with negative pressure adsorption, the key problem and future development of the wall climbing robot are put forward. Results: The patents of the wall climbing robot with negative pressure adsorption are classified in the paper. Studies show that remarkable improvements have been achieved in the invention on the climbing robot. Conclusion: In the tomorrow, the adsorption technology, optimization of moving mode, structure miniaturization and intelligent control should be further studied.
Keywords: obstacle crossing